Negative Regulation of VEGF Signaling in Human Coronary Artery Endothelial Cells by G Protein‐Coupled Receptor Kinase 5 - Zhou, Rui‐Hai (Clin Transl Sci, 2008)
G protein‐coupled receptor kinase 5 (GRK5) is present in endothelial cells (ECs) and has the potential to regulate EC function through seven transmembrane‐spanning receptor (7TMR) signaling. Recently, it has been appreciated that GRKs can affect receptor tyrosine kinases (RTKs). VEGF, an RTK, is one of the most potent mediators for EC function and angiogenesis; therefore, we determined the role GRK5 plays in VEGF signaling in human coronary artery ECs (HCAECs). GRK5 levels were increased by VEGF treatment in HCAECs. Adenoviral overexpression of GRK5 inhibited migration and proliferation of HCAECs in response to VEGF. GRK5 overexpression in HCAECs significantly suppressed both acute and late activation of Akt and extracellular signal‐related kinase (ERKs) as well as the phosphorylationof GSK‐3β, an endogenous substrate of Akt. Coimmunoprecipitations revealed that GRK5 is physically associated with Akt. This study shows for the first time that GRK5 negatively regulates VEGF signaling in HCAECs and suggests that targeted intervention of GRK5 in ECs might be a novel therapeutic strategy to prevent and treat disorders involving altered EC function.